The Effectiveness of Blended-Based Training on Teachers Competence in Padang Lawas District - Albert Efendi Pohan; Pandhit Isbianti (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
This study aims to determine the effectiveness of blended-based training on improving the teachers competence to act their main roles in preparing appropriate learning administration. The research was conducted in Padang Lawas Regency North Sumatra. To achieve the objective, pre-experimental research by one-group pre-test and post-test design was adopted. Research subjects were from teachers in Padang Lawas District with 31 teachers. The instrument which was used was a portfolio and individual test by writing the lesson plan and all tasks collected by google drive. The data analysis technique was performed using SPSS Statistic 20 by one simple paired t-test. The finding showed that blended-based training had a significant difference of values where the post-test score was bigger than the pre-test score where the significant value (2-tailed) was 0.000.05 could improve the teachers’ professionalism. Thus, blended training can improve teacher professionalism in Padang Lawas District.